Variational Inequalities for Systems of Strongly Nonlinear Elliptic Operators of Infinite Order (Global Journal of Science Frontier Research, 2018)
Abstract not found
Keywords: systems of strongly nonlinear elliptic operators of infinite order-variational inequalities